Sequential fixed-width confidence interval for the rth power of the exponential scale parameter: Two-stage and sequential sampling procedures. Issue 3 (3rd July 2018) - Lalehzari, Reihaneh; Mahmoudi, Eisa; Khalifeh, Ashkan
Abstract: In this paper, we study two-stage and sequential sampling procedures for estimating the r th power of the exponential scale parameter, i.e., β r, where the fixed-width confidence interval is considered. The exact operating characteristics of sequential procedures for fixed-width, 2 δ (δ > 0 ), confidence interval estimation is given. We show that the results of Zacks (2009 ), for two-stage and sequential procedures, can be deduced from our general results.